If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + x = 6(x) Solving 6 + x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 6 + x + -6x = 6x + -6x Combine like terms: x + -6x = -5x 6 + -5x = 6x + -6x Combine like terms: 6x + -6x = 0 6 + -5x = 0 Add '-6' to each side of the equation. 6 + -6 + -5x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -5x = 0 + -6 -5x = 0 + -6 Combine like terms: 0 + -6 = -6 -5x = -6 Divide each side by '-5'. x = 1.2 Simplifying x = 1.2
| [(5x+3)(8x+6)][(-9x+10)(144x+5x-5)]=y | | (B/5)=1 | | 12=4x^2 | | 1/2x^2-1/6x=1 | | -9p-3(6-5p)=2(p-3)-32 | | 4x+12=8x+24 | | 42+c=-c+3c-c | | (3/5)*(4/10) | | x1+x2=-3/2 | | 2/x+12-4/x-12=4x/x^2-144 | | 7y=-3x | | 1/3q=5/24 | | -5+8(7a+5)=-21 | | x^2+11=71 | | 3/5x4/10 | | 5x-(3x-4)=16 | | 3.8/0.8 | | 0.14x+0.7(x-1)=0.01(5x-3) | | 4y=-5x+8 | | 1/2(x+8)+3=18 | | 0.18x+0.3(x-3)=0.01(4x-3) | | 2-6=5 | | 6x^2+10x-64=0 | | 5g+4(-5+g)=1-g | | Y/5+8=7 | | 1/4x-1/5(x-7)=5x | | 2x+1/3y=2 | | -18k-6k=6+18k | | 1/4x+y=5 | | 61+x=36 | | 108=2x+20+2x | | x^3+6x^2-7x-42=0 |